Civil Capacities for Peace Support Operations: The Case of Bosnia and Herzegovina - Dizdarević, Emsad (Journal of Regional Security, 2018)
Bosnia and Herzegovina (BiH) has gone from being a receiver to providing assistance to post-conflict countries. Through its experience with rebuilding the country after conflict, BiH can make relevant and useful contributions to further peacebuilding and sustainable development in other countries. This article details current contributions BiH is making to international peace operations, maps the civilian capacities BiH could contribute in the future, and provides recommendations on how this could be implemented with regards to training, rostering and deployment of civilian capacities. Successful training, rostering and deployment of civilian capacities from BiH could be replicated at the Western Balkans level and bear witness to the development of security communities in BiH and the region.